Incidental finding of ectopic pancreatic tissue in gastric wall during laparoscopic sleeve gastrectomy: a case report - Hamdi, Hafiz A.; Abdo, Mohammed Y.; Alzahrani, Khalid M. (International Surgery Journal, 2024)
Ectopic pancreatic tissue, or heterotopic pancreas, is a rare congenital anomaly defined by the presence of pancreatic tissue outside its usual location and without vascular or ductal continuity with the main pancreas. It is often asymptomatic and typically discovered incidentally during imaging or surgical procedures. We report the case of a 41-year-old female undergoing laparoscopic sleeve gastrectomy for morbid obesity (BMI: 44 kg/m²), during which a 17×9 mm nodular lesion was identified on the anterior stomach wall. Histopathological analysis confirmed ectopic pancreatic tissue, classified as Heinrich type I. This case highlights the importance of recognizing incidental findings during bariatric surgery and the need for thorough pathological evaluation to rule out malignancy or other complications.